The needs and experiences of skin cancer patients: a qualitative systematic review with meta-synthesis - Bath-Hextall, Fiona; Nalubega, S.; Evans, Catrin (Wiley, 2017)
Background: Skin cancer incidence is increasing worldwide. This is an update of a previous review published in 2010 that identified only two studies and found that the needs and experiences of individuals with skin cancer were under-researched. Objectives: To undertake a qualitative systematic review of the needs and experiences of people with a diagnosis of skin cancer. Methods: As an update of a previous review, the following databases were searched from 2010 to 30/11/15: CINAHL PsycINFO, MEDLINE and EMBASE. The methodological quality of the studies was assessed using the Joanna Briggs Institute (JBI) Qualitative Assessment Review Instrument (QARI). The qualitative research findings were synthesised using a pragmatic meta-aggregative approach. Results: Fourteen studies (16 papers) were included. Only three studies included keratinocyte carcinoma patients. 15 categories were identified and these resulted in four overarching synthesised findings (SFs) from diagnosis (SF1) through treatment (SF2) and follow up (SF3), and then a fourth SF (SF4) that addressed patients’ satisfaction with their care and their relationship with health professionals. Conclusions: Despite the fact that keratinocyte carcinoma and melanoma patients can have very different prognosis, they also share similar needs and concerns especially around the time of diagnosis and follow up/surveillance for new lesions. Health professionals working with skin cancer patients need to understand their psychosocial concerns, and their information needs in order to design services appropriately. Future studies need to consider keratinocyte carcinoma patients as well as melanoma patients.